Literature Review: Analisis Metode Karyawisata Dalam Pembelajaran IPS Terhadap Hasil Belajar - Izky Kusumaningrum; Desy Safitri; Sujarwo Sujarwo (Lembaga Pengembangan Kinerja Dosen, 2024)
As one of the educational factors, methods play a role that is no less important than other factors. There is not a single learning activity that does not use methods. Methods are also adapted to the interests of students, one example of a method is field trips. This review aims to see how effective this field trip method is on student learning outcomes. This review was prepared based on a literature review or literature study. The data obtained comes from reviews of books, journals and articles on similar topics. The results of this review show that the field trip method is effective in learning and also influences student learning outcomes.